Accelerated corrosion behavior of weathering steel Q345qDNH for bridge in industrial atmosphere. (1st November 2021) - Fu, Jun-dong; Wan, Shui; Yang, Ying; Su, Qiang; Han, Wen-wen; Zhu, Ying-bo
Highlights: A new type of weathering steel Q345qDNH with different alloy content is used in bridge construction. The corrosion resistance of weathering steel Q345qDNH is better than that of standard carbon steel Q345qD. The corrosion resistance mechanism of weathering steel Q345qDNH has been studied in detail. Abstract: Weathering steel (WS) has an extensive use in steel bridge construction thanks to its satisfactory atmospheric corrosion resistance, low life cycle cost and good mechanical properties. In this paper, cyclic immersion corrosion experiment was carried out in simulated industrial atmospheric environment. The corrosion weight loss, macro morphology, rusting coat section, XRD and electrochemical characteristics of bridge weathering steel Q345qDNH and low alloy steel Q345qD were compared. The corrosion characteristics were identified and underlying corrosion inhibition mechanism of bridge weathering steel Q345qDNH were analyzed. The experiment and analysis results show that the rusting coat on the exterior of standard carbon steel is relatively loose and porous, and the main component is Fe3 O4 . The rusting coat of weathering steel is divided into internal and external layers under atmospheric corrosion, the outer rusting coat is loose primarily composed of γ – FeOOH and the inner rusting coat is uniform and dense, principally containing α – FeOOH. During the evolution of the rusting coat, the addition of trace alloy elements in weathering steel effectively promoted the transformation from γ – FeOOH to α – FeOOH, forming a more stable and condense inner rusting coat. It can potently isolate the corrosive medium from penetrating in and enhance the electrochemical corrosion resistance of rusting coat, so it possesses better corrosion resistance in atmospheric corrosion environment and has a promising application prospect in bridge engineering construction.